Interpretasi Sebaran Mineral Nikel Menggunakan Metode Geomagnet di Desa Tambale Kecamatan Mamosalato - Hermanto, Yudi; Efendi, Rustan; Abdullah, Abdullah (Gravitasi, 2017)
ABSTRACTÂ Research on the interpretation of distribution of nickel minerals using geomagnet method in Tambale Village, Mamosalato District have been done. This research to interpretation the distribution of nickel minerals by analyzing the distribution of the nickel mineral carrier rocks. Stages of research include; data acquisition, IGRF correction and daily variation correction, separation of magnetic anomalies to residual magnetic anomalies, and modeling. The modeling technique used is 3D inversion modeling technique using MAG3D software. Suseptibility of rocks carrier of nickel minerals between 0.07540 SI to 0.16336 SI. Susptibility is suspected as ultramafic rocks namely peridotite and dunit and metamorphic rocks namely serpentine. The distribution of sueptibility in the south to the north and tend to spread to the east of the study location with an average depth of approximately 60 meters under front of the ground.Keywords: Anomaly, Magnetic, Inversion modelling, Suseptibility